Living the great illusion : Sir Norman Angell, 1872-1967 - Ceadel, Martin (Oxford : Oxford University Press, 2009)
This biography of one of the 20th century's leading internationalists, Sir Norman Angell, author of 'The Great Illusion', Labour MP, and winner of the Nobel Peace Prize, reveals that his life has hitherto been much misrepresented and misunderstood.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Angell, Norman, -- 1874-1967.; Internationalists -- Great Britain -- Biography; Nobel Prize winners -- Biography; International relations